Respons Verbal dan Nonverbal Siswa Terhadap Komunikasi Guru dalam Pembelajaran Puisi - Lestari, Vonny Tri; Riyanto, Agus; Triana, Leli (Universitas Muhammadiyah Magelang, 2025)
This study aims to describe students' verbal and nonverbal responses to Indonesian language teachers' interpersonal communication strategies in poetry learning. This study used a qualitative descriptive approach with observation, interview, and documentation techniques. The results showed that students provided verbal responses in the form of answers, questions, and opinions that reflected active involvement in the learning process. In addition, nonverbal responses such as nods, smiles, body movements, and facial expressions also appeared as forms of emotional involvement and readiness to learn. Both forms of response indicate that the teacher's communication was able to create a dialogic learning atmosphere, supporting and encouraging students to express themselves optimally in poetry learning.